Your favorite Seuss 13 stories written and illustrated by Dr. Seuss with 13 introductory essays - Seuss Dr.; Schulman, Janet; Goldsmith, Cathy; Seuss Dr. (New York Random House Children's Books, 2004)
A compilation of more than a dozen previously published Dr. Seuss books, plus essays by nine authors and other book lovers, including Audrey Geisel, widow of Dr. Seuss.
Who is Dr. Seuss? / by Janet Schulman -- He is everybody's inner child / by Barbara Bader -- And to think that I saw it on Mulberry Street -- You're never too old / by Stan and Jan Berenstain -- McElligot's pool -- Thank you, McGrew / by John Lithgow -- If I ran the zoo -- A gift worth waiting for / by Christopher Cerf -- Horton hears a who! -- And enter the cat / by Christopher Paolini -- The cat in the hat -- The true spirit of the Grinch / by Charles D. Cohen -- How the Grinch stole Christmas -- Yertle, Hitler, and Dr. Seuss / by Richard H. Minear -- Yertle the turtle -- No holiday is more important / by Barbara Mason -- Happy Birthday to you! -- We love Sam / by Starr LaTronica -- Green eggs and ham -- He taught us how to think / by Peter Glassman -- The Sneetches -- Looks like something from Seuss! / by Lane Smith -- Dr. Seuss's sleep book -- Love it or lose it by Pete Seeger ; with the Environmental Club of Our Lady of Lourdes High School -- The Lorax -- Living with the cat / by Audrey Geisel -- Oh, the places you'll go!
Keywords: Humorous stories, American; Children's stories, American; Humorous stories; Stories in rhyme; Short stories